Improvement of mechanical properties of railway track concrete sleepers using ultra high performance concrete (UHPC) - Sayed Ahmed; Hossam Atef; Mohamed Husain (Fracture and Structural Integrity)
In recent times, the shape of the beams evolved from wooden sleepers and then to steel sleepers until they reached concrete sleepers. These sleepers play a significant role in transferring the loads from the train wheels to the subgrade layers fixed by the railway. This development took place in concrete sleepers until we reached mono-block concrete sleepers. This paper discusses, through laboratory experiments, the effect of ultra-high performance concrete mixtures on the behavior of mono-block concrete sleeper B70. The ability of these new sleepers to resist train loads was also studied compared to its conventional concrete sleepers. This research aimed to determine through experiment if these sleepers' behavior fulfilled the European requirements standers for prestressed concrete sleepers and make comparisons between the UHPC sleepers and conventional concrete sleepers. These sleepers were tested under static load tests at the rail seat and center section and pull-out tests for cast-in fastening components. These initial results suggest that a new generation of Ultra-high performance concrete sleepers can be created; the long-term efficiency of this category of sleeper will need to be confirmed by dynamic and fatigue tests and practical use.